De Mattos, C.; Figueroa, L.; Bannen, P. y Campos, D. (Editores). Santiago en EURE. Huellas de una metamorfosis metropolitana 1970/2000 - Fuentes, Luis (Revista de Geografía Norte Grande, 2006)
No presenta resumen